2021
DOI: 10.1007/s40273-021-01008-7
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Published Health Economic Obesity Models: Assessment of Facilitators, Hurdles and Reproduction Success

Abstract: Objectives This research aims to (1) replicate published health economic models, (2) compare reproduced results with original results, (3) identify facilitators and hurdles to model replicability and determine reproduction success, and (4) suggest model replication reporting standards to enhance model reproducibility, in the context of health economic obesity models. Methods Four health economic obesity models simulating an adult UK population were identified, selected for replication, and evaluated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…As basis for this research, three previously replicated obesity models were used [9][10][11][12][13]. These models reflect three main structural obesity event simulation approaches commonly used in health economic obesity modelling [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As basis for this research, three previously replicated obesity models were used [9][10][11][12][13]. These models reflect three main structural obesity event simulation approaches commonly used in health economic obesity modelling [8].…”
Section: Methodsmentioning
confidence: 99%
“…These models were selected on the basis of a previously published systematic review by our research group [ 8 ], and on the basis of minimal quality requirements based on an expert consensus [ 12 ]. All models were previously successfully replicated in TreeAge Pro (Version 2021 R1.1) on the basis of the published data [ 13 ]. For assessing the success of the model replications, we applied different criteria as defined and proposed in a recently published review on this topic [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Simulation approaches built upon reproducible research allow for the construction of accurate prediction models with important implications for healthcare [ 83 ] and public health [ 84 ]. In the same way, reproduction and replication of results for model validation are essential [ 85 , 86 , 87 ].…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Obesity is a prevalent issue worldwide and is a significant public health concern [ 1 , 2 ]. It has been demonstrated that obesity can have adverse effects on mammalian reproductive capacity [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%